2007
DOI: 10.4141/a06-070
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient digestibility, fecal output and eating behavior for different cattle background feeding strategies

Abstract: . 2007. Nutrient digestibility, fecal output and eating behavior for different cattle background feeding strategies. Can. J. Anim. Sci. 87: 393-399. To examine the effects of limit feeding a high-grain barley-based diet to growing cattle on nutrient digestibility, fecal DM out put and eating behavior, sixteen crossbred steers (326 ± 42.1 kg) housed in individual indoor pens were fed one of two feeding regimes in a randomized complete block design. Dietary treatments included a high-grain diet containing 1.94 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
2
5
0
1
Order By: Relevance
“…This was in accordance with Van Soest (1994) that the development of microbes in digesting feed is very dependent on the ingredients of feed intake. The results of this study were similar to Klinger et al (2007), who reported that in cattle fed with higher content of fibre causes higher crude fibre digestibility value compared with feed containing lower fibre.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 90%
“…This was in accordance with Van Soest (1994) that the development of microbes in digesting feed is very dependent on the ingredients of feed intake. The results of this study were similar to Klinger et al (2007), who reported that in cattle fed with higher content of fibre causes higher crude fibre digestibility value compared with feed containing lower fibre.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 90%
“…Similar results were found by Klinger et al, (2007) reported different type of feeding had significant effect (P<0.05) on rumination time in cattle while Grewal (1980) observed that there was no significant difference in rumination time between two levels of concentrates. McCleod et al, (1994) [10] observed that the time spent on rumination was not affected by feeding sequence of hay averaging 428 minutes and rumination tended to occur when there was no eating activity.…”
Section: Treatmentssupporting
confidence: 85%
“…Yazdani (1996) who observed non significant higher eating time in thatched roof house as compared to loose house in crossbred calves. The contrary results were found by Klinger et al, (2007) reported different type of feeding had significant effect (P<0.05) on eating time in cattle.…”
Section: Eating Timementioning
confidence: 59%
“…Projection of liveweight gain (1.22 kg d -1 ) for the ad libitum-fed high-forage cattle and the amount of DM required for the limit-fed high-grain cattle to achieve the same rate of gain were based on the DMI equations for large-frame steers (NRC 1984) and a subset of the net energy of maintenance and gain equations (NRC 1996). The equations used for prediction are given in our companion paper (Klinger et al 2007). The simpler approach of NRC (1984) was chosen over the more detailed approach of NRC (1996) as environment, pen conditions and management were similar for all cattle.…”
Section: Animal and Nutritional Managementmentioning
confidence: 99%